2020
DOI: 10.1097/pcc.0000000000002325
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine for Prolonged Sedation in the PICU: A Systematic Review and Meta-Analysis*

Abstract: Objectives: We aimed to systematically describe the use of dexmedetomidine as a treatment regimen for prolonged sedation in children and perform a meta-analysis of its safety profile. Data Sources: PubMed, EMBASE, Cochrane Library, Scopus, Web of Science, ClinicalTrials.gov, and CINAHL were searched from inception to November 30, 2018. Study Selection: We included studies involving hospitalized critically il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The recently published clinical practice guidelines for the management of Pain, Agitation, Neuromuscular Blockade, and Delirium in critically ill pediatric patients with consideration of the PICU Environment and Early Mobility (PANDEM) and the Recommendations for analgesia and sedation in critically ill children admitted to intensive care unit [ 8 , 19 ] both recommend the use of alpha 2 -agonists over benzodiazepines as a first-line sedative. It has been shown that alpha 2 -agonists is a safe and benzodiazepine sparing alternative for sedation in the pediatric population [ 20 22 ]. We could reveal that only as much as 11% of the responding PICUs in Europe would use dexmedetomidine as a first-choice sedative and only 7% opted for clonidine.…”
Section: Discussionmentioning
confidence: 99%
“…The recently published clinical practice guidelines for the management of Pain, Agitation, Neuromuscular Blockade, and Delirium in critically ill pediatric patients with consideration of the PICU Environment and Early Mobility (PANDEM) and the Recommendations for analgesia and sedation in critically ill children admitted to intensive care unit [ 8 , 19 ] both recommend the use of alpha 2 -agonists over benzodiazepines as a first-line sedative. It has been shown that alpha 2 -agonists is a safe and benzodiazepine sparing alternative for sedation in the pediatric population [ 20 22 ]. We could reveal that only as much as 11% of the responding PICUs in Europe would use dexmedetomidine as a first-choice sedative and only 7% opted for clonidine.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, observed concentrations increased with dexmedetomidine infusion rates, as shown in Figure 1 . Considering that the maximum dosing rate in our study was 1.1 mcg/kg/h, our results suggest that the proposed threshold of concentration >700 pg/mL is attainable in children on ECMO while staying within the dosing range of 0.1 and 2.5 mcg/kg/h reported in critically ill children ( 35 ). However, the exact dexmedetomidine concentrations leading to adequate sedation in an acute care setting remain to be determined, especially in children on ECMO, considering the more invasive equipment and severity of the disease contributing to greater discomfort.…”
Section: Discussionmentioning
confidence: 51%
“…11,12 However, a systematic review including 32 studies using DEX infusion in the PICU showed that only five studies reported the use of DEX as an adjuvant for weaning, and only two described its use for treatment of WS. 22 In a recent prospective multicenter study (PROSDEX) including 163 pediatric patients, DEX was confirmed to be used both for prevention of WS (12% of patients) and as an adjuvant for its treatment (15%).…”
Section: Discussionmentioning
confidence: 99%